Reading and Understanding Texts - Podlasińska, Ilona (Glottodidactica, 2008)
The ability to read effectively is essential to the success in life. Unfortunately many students experience difficulty in mastering this skill. That is why in this article I have presented certain techniques which can help to develop and improve the students' reading skills. Reading is widely considered to be a passive process whereas it is an active and involving one. To be able to read effectively, the reader must work out what they want to achieve and how well they are progressing. Reading is an active and interactive process involving many skills. Therefore the teacher's role in enhancing the reading skills is enormous.